Annual Plan 1979-80 Government of India Planning Commission - Planning Commission (Planning Commission, 1980)
The Annual Plan 1979-80, part of India’s Fifth Five-Year Plan, emphasized sustainable economic growth, employment generation, and social welfare. With a total public sector outlay of Rs. 12,601 crores, the plan prioritized agriculture, rural development, industrial expansion, power generation, and social programs for disadvantaged groups. Key initiatives included irrigation and cooperative sector improvements, the Integrated Rural Development and Food-for-Work programs, and investments in energy, coal, petroleum, chemicals, fertilizers, and heavy industry. Employment projections indicated substantial job creation across agriculture, manufacturing, services, and infrastructure sectors. The plan also allocated funds for communications, water supply, housing, nutrition, and SC/ST development through Tribal and Special Component Plans. Rehabilitation programs for displaced persons were supported with targeted funding. Overall, the plan reflected a comprehensive strategy to enhance productivity, generate employment, strengthen infrastructure, and improve socio-economic conditions for marginalized communities while maintaining fiscal discipline and monitoring sectoral performance.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Annual Plan; Fifth Five-Year Plan; Economic Growth; Agriculture; Industry; Employment Generation; Rural Development; Social Welfare; Infrastructure; Energy; Minerals; Rehabilitation; SC/ST Development